2006
DOI: 10.1038/sj.npp.1301262
|View full text |Cite
|
Sign up to set email alerts
|

Acute Serotonin and Dopamine Depletion Improves Attentional Control: Findings from the Stroop Task

Abstract: Schizophrenia is associated with impairments of attentional control on classic experimental paradigms such as the Stroop task. However, at a basic level the neurochemical mechanisms that may be responsible for such impairments are poorly understood. In this study, we sought to investigate the influence of brain monoamine function on Stroop task performance in healthy participants using the established methods of acute dietary serotonin, dopamine, and combined monoamine depletion. The study was a double-blind p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 102 publications
7
48
2
Order By: Relevance
“…These findings suggest that serotonin loss enhances salience of stimuli associated with reward as in the case of both the rodent and human 5-CSRTT. This general conclusion appears valid for the effects of TD in other test situations in humans, as, for example, TD-enhanced performance in Stroop test (Scholes et al, 2007). A further effect of TD in the human 4-CSRTT was to increase a 'motivational index', which was derived from the difference in RT of baseline test blocks separated by the block where error feedback was provided.…”
Section: Effect Of Serotonin Depletion On Accuracy and Motivational Imentioning
confidence: 93%
“…These findings suggest that serotonin loss enhances salience of stimuli associated with reward as in the case of both the rodent and human 5-CSRTT. This general conclusion appears valid for the effects of TD in other test situations in humans, as, for example, TD-enhanced performance in Stroop test (Scholes et al, 2007). A further effect of TD in the human 4-CSRTT was to increase a 'motivational index', which was derived from the difference in RT of baseline test blocks separated by the block where error feedback was provided.…”
Section: Effect Of Serotonin Depletion On Accuracy and Motivational Imentioning
confidence: 93%
“…Acute tyrosine/phenylalanine depletion (ATPD) has been shown to selectively decrease DA synthesis and release (Leyton et al 2004;McTavish et al 1999aMcTavish et al , b, 2001aMehta et al 2005;Montgomery et al 2003), and impair DA-dependant cognitive processes such as working memory (Harmer et al 2001;Harrison et al 2004). Finally, CMD has been shown to simultaneously deplete tryptophan, tyrosine and phenylalanine to levels that are expected to modulate central serotonergic and dopaminergic function ) and modulate cognitive and sensory processes related to 5-HT and DA functions Scholes et al 2007;Mann et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Harrison and colleagues 64 demonstrated that ATD but not APTD impaired declarative memory in healthy women. Scholes and colleagues 65 found that ATD and APTD, but not the combined depletion, decreased Stroop interference in healthy men, indicating increased attentional control. Finally, Mann and colleagues 66 studied healthy men who showed disruption of prepulse inhibition after ATD, but not after APTD.…”
Section: The Need For Positive Control Treatments and Other Strategiementioning
confidence: 99%